Factor Content of Agricultural Trade - d'Artis Kancs; Pavel Ciaian (Economics and Econometrics Research Institute (EERI), 2008)
In this paper we study factor content of the CEE agricultural trade. In order to account for differences in technology and factor prices in CEE, the theoretical framework of the present study builds on the previous work of Helpman (1984) and Staiger (1986) who consider a trade equilibrium in which factor prices are allowed to differ across countries and Lai and Zhu (2007), who account for international technology differences. In the empirical analysis we examine three hypothesis, which relate cross-country differences in technology, relative factor abundance and transaction costs and market imperfections to the factor content of trade. We find that the first two hypotheses are confirmed by the majority of developed countries, but rejected by roughly one half of the CEE transition country pairs. We find that, when accounting for transaction costs of farm (re)organisation, both hypotheses are confirmed by the majority of CEE country pairs. These findings provide empirical evidence of market imperfections, and particularly, of transaction costs of farm (re)organisation.
Keywords: F12; F14; D23; Q12; Q17; 330; Factor content; bilateral trade; relative factor abundance; technological differences; agriculture; transaction costs